Challenges of scale-up to dolutegravir-based regimens in sub-Saharan Africa. (1st April 2020) - Salou, Mounerou; Butel, Christelle; Comlan, Adjo S.; Konou, Abla A.; Tegueni, Kokou; Ehlan, Amivi; Lack, Fiali; Dossim, Sika; Ayouba, Ahidjo; Delaporte, Eric; Dagnra, Anoumou Y.; Peeters, Martine
Abstract : Objective: Evaluate the potential effectiveness of the implementation of dolutegravir (DTG)-based regimens in patients on failing current antiretroviral treatment (ART) given the high levels of nucleoside reverse transcriptase inhibitor (NRTI) resistance in Togo. Design: Patients on ART attending health facilities for routine follow-up visits and for whom HIV viral load test was performed were consecutively included. Methods: Protease, reverse transcriptase and integrase fragments were sequenced and analyzed for presence of drug resistance mutations for patients with viral load more than 1000 copies/ml. Results: Among 1681 patients, 320 (19.04%) had viral load more than 1000 copies/ml and 200 were tested for drug resistance mutations. Reverse transcriptase gene was successfully sequenced for 181/200 (90.5%) patients; 140/181 (77.4%) were resistant to NRTIs and non-NRTIs, 4/181 (2.2%) to NRTIs only and 18/181 (9.9%) to non-NRTIs only. Many viral strains accumulated mutations predicting resistance to NRTIs recommended in first and second-line DTG-based ART regimens. ART switch to a DTG-based regimen after viral load testing (viral load >1000 copies/ml) or blind switch without prior viral load testing to a new DTG-based first line, estimated 31% and 47.6% of patients to be potentially on functional DTG monotherapy respectively. Conclusion: Overall, our results predict that, at the scale of sub-Saharan Africa a significant proportion of patients could be on functional monotherapy. To achieve the third 90 of UNAIDS objectives, implementation of DTG-based regimens should be accompanied with an accelerated scaling up of access to viral load. Studies designed to quantify the implications of use of suboptimal DTG-based regimens are also needed. Abstract : Supplemental Digital Content is available in the text